Phytochemical of Chromolaena odorata - Ganesan, Mala (2018)
C.odorata is commonly consumed as traditional medicine in some countries, including Malaysia. This study was aimed to identify the extractive values in C.odorata on a different type of solvents and parts of plants and analyzed its total phenolic contents (TPC) and phytochemical using Gas chromatography-mass spectrometry (GC-MS). In comparison with different solvents in parts which are leaf and stem extracts of C.odorata had the significantly different in yield of extraction and TPC, respectively. Among that, the leaf of this species had a great yield than the stem. The hot water extract on the leaf was found has the highest yield with hot water (27.96%) followed by methanol (26.56%), ethanol (26.33%), cold water (24.96%), and petroleum ether (5.54%) respectively. In the stem, the most extractive value was found in hot water (18.53%), followed by methanol (15.06%), cold water (13.46%), ethanol (12.40%), and petroleum ether (0.79%) respectively. In TPC, the leaf of this species had highest amount of phenolic compounds with hot water (331.80 ± 5.92 mg GAE/g DW) followed by methanol (318.71 ± 1.67 mg GAE/g DW) and petroleum ether (125.13 ± 8.84 mg GAE/g DW) and in stem the highest amount of phenolic compound was found in hot water(315.73± 2.37 mg GAE/g DW ) followed by methanol (221.67 ± 0.01 mg GAE/g DW) and petroleum ether (12.84 ± 4.66 mg GAE/g DW). GCMS analysis of the leaf showed the presence of fatty acids, glycerides, sugar alcohols, alcohols, alkanes and chlorine compounds, and for the stem presence of alkanes, which contribute to its antioxidants agents.